ACCEPTABILITY OF MILKFISH (CHANOS-CHANOS) SAUSAGE: TECHNO-GUIDE FOR INSTRUCTION AND EXTENSION ACTIVITIES - Villagonzalo, Josephine M (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 3-4, 2008, 2008)
The study aims to promote and introduce milkfish that will meet consumers acceptability as an alternative way of preparing fish sausage other than the traditional use of pork or beef, geared towards livelihood and technoguide in the College Extension Program. Recipe A, (Milkfish with bell pepper) was acceptable with 8.26 weighted mean. Recipe B, (Milkfish sausage with hot pepper) was very much liked with 8.57 weighted mean received a better rating with a difference of .31. The F – Distribution of the following attributes: color 44.90; odor / smell 0.14; flavor, 58; texture 8.84; and the general acceptability, 1.69. Thus, HO is accepted. The formulated milkfish sausage with bell pepper and with hot pepper was found to be “liked very much”. The formulation could be viable for production, with commercial intent.